Crop safety and control of acetolactate synthase inhibitor-resistant Palmer amaranth (Amaranthus palmeri) with very long-chain fatty acid-inhibiting herbicides in dry edible bean - Miranda, Joshua W. A.; Jhala, Amit J.; Bradshaw, Jeffrey; Lawrence, Nevin C. (Frontiers in Agronomy, 2024)
Palmer amaranth is a relatively recent arrival in Western Nebraska, where acetolactate synthase (ALS)−inhibitor−resistant biotypes are common in the region. With limited effective postemergence (POST) herbicides for controlling ALS−inhibitor−resistant Palmer amaranth in dry edible bean, a sequential preemergence (PRE) followed by (fb) POST program of very long-chain fatty acid (VLCFA)−inhibiting herbicides shows promise. Currently, dimethenamid−P is the only VLCFA−inhibiting herbicide registered for POST use in dry edible bean in Nebraska. The objective of this study was to assess the crop safety and effectiveness in weed control of sequential PRE fb POST programs, including pendimethalin + dimethenamid−P applied PRE fb dimethenamid−P POST, pendimethalin + S−metolachlor PRE fb S−metolachlor POST, and pendimethalin + pyroxasulfone PRE fb POST, in comparison with pendimethalin + dimethenamid−P applied PRE fb imazamox + bentazon + fomesafen applied POST in dry edible bean. Results showed that sequential PRE fb POST programs were more effective in reducing both the density and biomass of Palmer amaranth compared to PRE-alone programs. Pendimethalin + dimethenamid−P applied PRE fb dimethenamid−P POST, along with pendimethalin + S−metolachlor PRE fb S−metolachlor POST, resulted in over 85% control of Palmer amaranth, similar to the effectiveness of pendimethalin + dimethenamid−P PRE fb fomesafen + imazamox + bentazon applied POST. Pendimethalin + pyroxasulfone applied PRE-alone and the application of pendimethalin + pyroxasulfone PRE fb pyroxasulfone POST showed inconsistent control of Palmer amaranth, causing high crop injury, stand loss, and delayed maturity, ultimately leading to yield loss. Dimethenamid−P and S−metolachlor demonstrated excellent crop safety when applied either PRE-only or sequentially. Pendimethalin + S−metolachlor PRE fb S−metolachlor POST provided control of Palmer amaranth comparable to that achieved with POST applications of dimethenamid−P and imazamox + bentazon + fomesafen.